Strategic analysis of uniquemark: the market entry of an innovative assay marking technology - international licensing for assay offices - Mello, Madalena Coelho dos Reis Mercês de (2023)
The project aims to design a comprehensive market entry strategy to successfully launch UniqueMark, an innovative hallmarking technology, into the market. This Work Project intends to assist Imprensa Nacional Casa da Moeda (INCM) in developing a strategic business plan, leveraging the technology’s value proposition and market opportunities. Internal and external analysis, incorporating best practices and concept testing, are the key phases of the methodology. The findings are organized among two main guiding pillars (price and place) that led to the recommendation of a customized strategy tailored to firm’s needs. Further research was suggested to better implement the final recommendations. Keywords: Strategy Consulting, Hallmarking, Assay Office, Jewelry, Authenticity, Traceability, Technology, Innovation, Precious Metals.